HAK PILIH (KHIYAR) DALAM TRANSAKSI JUAL BELI DI MEDIA SOSIAL MENURUT PERSPEKTIF HUKUM ISLAM - Moh. Ah. Subhan ZA. (Akademika, 2017)
Islam has taken into account the right to select (khiyar) in buying and selling transaction with the aim of avoiding possible fraud, forgery and so on so as to create a willingness between each party. Khiyar could be conducted when sellers and buyers meet directly physically as that in any buying and selling transaction. While in the modern buying and selling process done in cyberspace, especially in social media such transaction raises the question "what is the khiyar in the cyberspace transaction?" Although the transaction occurs two-side interaction, between the seller and the buyer both do not meet directly in one place and goods traded could not be held or reversed. Buyers could only see photos or video of goods to be purchased along with its prices. Based on the writer's study, it could be concluded that the buying and selling transaction in social media which although between the seller and the buyer both do not meet directly physically—only in the virtual world—the transaction is still considered in one majlis so the khiyar is still considered adequate and valid. Because the so-called one majlis should not be interpreted that both the seller and buyer are equally present in one place. But what is meant by one majlis is, the so-called ijab qabul is done within the time in a contract, in the sense that after the ijab is pronounced followed with the so-called qabul in a transaction or when pronouncing ijab qabul is not interspersed with other words which according to custom is assumed to be capable of interrupting it.